Role of temperature in biological control of tropical coccids in glasshouses - Copland, M. J. W. (Penerbit Universiti Pertanian Malaysia, 2013)
The mealybug Planococcus citri (Risso) and the soft scale Saissetia coffeae (Walker) were well known tropical pests and potential predators and parasitoids. However, there were no detailed studies on biological control of these pests in glasshoused. Preliminary trials suggested that the control workeds only during summer months when temperatures were well above 20 C. WE had investigated the potential of several parasitoid species and predatory beetle. We found that temperature was the main limiting factor. Egg, larval and pupal development; and adult egg production may proceed at quite low temperatures and adult longevity was increased provided individuals had the opportunity to feed. However, larval behavioural processes such as moulting, feeding and adult activity such as dispersal, host founding and egg laying were inhibited. Mating and sex determination seemed independent of temperature. While a constant 20 C may be too cold, successful control were achieved at lower mean temperatures by providing a few hours daily above 20 C. We selected species with the best temperature criteria and we defined a cyclical temperature regime which used the same amount of heating fuel yet provided a considerably improved performance of the biological control agents. This study had implications for biological control agents whereever they were used. It was essential to define the generation time, longevity fecundity and dispersiveness of a potential agent. Yet screening and experimentation at constant temperature will give a false picture of their performance in the field